Increasing Student Activeness in Online Learning with the Discovery Learning Model and Interactive Media - Any Inti Wahyu Setyaningrum (Universitas Sebelas Maret, 2020)
The purpose of this study was to increase student activeness in online learning with discovery learning models and interactive media for grade 4 students at SD Negeri 2 Karanganyar. The subjects were grade 4 SD Negeri 2 Karanganyar, totaling 9 students. The CAR design uses interactive media to increase student activeness in thematic subjects for grade 4 SD Negeri 2 Karanganyar students. Data collection techniques using observation and tests. The data analysis used descriptive quantitative and qualitative statistics. The results showed an increase in student activeness, this can be seen from the observation sheet of the pre-action activities and each cycle, namely in the pre-action it was 22.2%, in cycle I it was 55.6%, while in cycle II it was 88.9 %. This was accompanied by an increase in the average student learning outcomes from pre-action by 54.4, cycle I was 63.9, while in cycle II was 81.1. Thus it can be concluded that the use of interactive media can increase student activity in the Thematic learning of grade 4 elementary school students.